1991
DOI: 10.1152/ajpendo.1991.261.2.e199
|View full text |Cite
|
Sign up to set email alerts
|

Relative expansion of extracellular fluid in obese vs. nonobese women

Abstract: There is a conflict in previous studies with regard to the relation between adipose tissue mass and total body fluid distribution. This study tested the hypothesis that obesity is accompanied by an increase in the extracellular-to-intracellular fluid ratio above that observed in nonobese subjects. Extracellular fluid was evaluated in obese (n = 39) and nonobese (n = 26) healthy women, using two different dilution volumes, 35SO4 [extracellular water (ECW)] and 24NaCl [exchangeable sodium (Nae)]. Intracellular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
131
2
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 9 publications
8
131
2
2
Order By: Relevance
“…It would also draw attention on the effects of treatment (diuretics, etc) on metabolism. In obese patients where a extracellular expansion is demonstrated (Battistini et al, 1995;Waki et al, 1991), metabolic data would be useful to challenge the theory.…”
Section: Discussionmentioning
confidence: 99%
“…It would also draw attention on the effects of treatment (diuretics, etc) on metabolism. In obese patients where a extracellular expansion is demonstrated (Battistini et al, 1995;Waki et al, 1991), metabolic data would be useful to challenge the theory.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the physiological relationship between Wt and TBW may be altered in obese children and that factors other than Wt may be involved in the control of body water in obese subjects. This may be of pathophysiological importance since the altered water homeostasis of obese subjects is likely to play a role in the development of oedema and hypertension (Waki et al, 1991). In obese subjects, ZI is a better predictor of TBW than Wt.…”
Section: Discussionmentioning
confidence: 99%
“…Whether obese subjects have an altered body water distribution has been the subject of some controversy until the recent work of Waki et al (1991). These Authors have convincingly shown that obese women have a reduced body hydration and an expanded ECW:ICW ratio in comparison to control women.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to normal-weight women, obese women have a lower total body water (TBW) per unit of weight (Wt) and a higher extracellular water (ECW) per unit of TBW (Waki et al, 1991). This ECW : TBW expansion persists after weight loss and may be an intrinsic feature of obesity (Mazariegos et al, 1992;Van Marken Lichtenbelt & Fogelholm, 1999).…”
Section: Introductionmentioning
confidence: 99%